RENTAL INFORMATION AND PAYMENT SYSTEM COMPACT VIDEO DISK (VCD) VCD RENTAL HOPE IN USING VISUAL BASIC 6.0 - Hariyadi Hariyadi; Irfan, SKom, MMSI Irfan, SKom, MMSI (Jurnal Sistem Informasi, 2003)
Writing is about the problems that arise in payment systems and VCD rentals. The author proposes a system of payment of rental and for solving problems in the rental and payment system in which tenants are petrified to collect data. This system is used to improve the effectiveness and quality of the writing section is proof of payment.  This system stores data for the tenant's payment and process the data into a daily report.